PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH TABUNGAN BANK SYARIAH - Fansuri , Deni; Zulfison, Zulfison (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to discuss the influences that affect customer satisfaction of Islamic bank savings. The independent variables obtained from the results of the preliminary survey are Service Quality, Product Quality and Customer Value. While the dependent variable obtained is customer satisfaction. The analysis test includes the normality test, linearity test, and multicollinearity test. Hypothesis testing using multiple regression. The population in this study were customers of Islamic banks, with a sample of 106 respondents using Islamic bank savings. The sampling technique used purposive sampling. By using a quantitative descriptive approach. The results of this study indicate that service quality has no significant positive effect on customer satisfaction, product quality has a significant positive effect on customer satisfaction, customer value has a significant positive effect on customer satisfaction.